Social capitals as village building potential (Case study: Matamppa Walie Village Community in Bone Regency) - Sabiq, Muhammad; Sakaria, Sakaria; Arisnawawi, Arisnawawi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
Kinship among the people of Mattampa Walie village in Bone can be created because values, norms and trust between fellow communities are still upheld. The concept of social capital has three important elements, namely trust, values and networks, which can place special emphasis on the causal relationship between social capital and community welfare. The research uses a qualitative approach with a case study type. Data collection was carried out using observation, interview and documentation techniques. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The research results show that strong social capital, supported by trust, solid social networks, and the values of mutual cooperation, is an important foundation in strengthening solidarity and togetherness in the Mattampa Walie Village community. It is hoped that this will be an impetus for better development, as well as increasing the welfare and resilience of families in preparing strong human resources.